"Impossibility of its being deciphered": Anne Lister, her "crypt hand" diaries, and the contrast between voicing and silencing. Issue 4 (18th November 2022) - Hamilton, Rebecca
Abstract: In recent decades, it has become increasingly important to reevaluate certain literature and figures in history to discover what was being communicated in the midst of, and through, the silence of minority groups. My particular focus is on the tradition of white female silence and the ways in which Anne Lister and her diaries (as separate entities) contributed to conversations about silence by establishing other methods of communication despite restrictions placed on women's voices at the time. As the main focalizers in the creation and depiction of her societal and sexual identity, I discuss Lister's "crypt hand" diaries, her self-presentation, her inheritance of Shibden Hall, and the contrast they offer between voicing and silencing. Although I argue that through these focalizers Lister does present a certain level of voicing or speaking out, ultimately this is done by using various methods of silence such as coding and implication. I also offer particular analysis of Lister's conceptualization of her own sexuality compared with that of the women she sleeps with and how her inability to fathom their queer identities contributes to a narrative of oppressive patriarchal silence.